The Croatian standardisation of the MMPI-2 - Matešić, Krunoslav; Pinjušić, Katarina (2007)
The aim of the research was to collect normative data for the Minnesota Multiphasic Personality Inventory (MMPI-2). The translation and adaptation of the Inventory were conducted on the principle of forward and back translation: the Inventory was first translated into Croatian, following which a translator not familiar with the English original, translated the text back into English. The Restandardization Committee of the University of Minnesota Press commended the quality of our translation. The normative data were collected on a sample of 587 subjects, aged between 18 and 86, from all regions of Croatia. Of the total number of subjects 55.7% (N = 327) were females and 44.3% (N = 260) were males. Data were also collected on a clinical sample of 126 subjects, 64 males and 62 females, aged between 18 and 69. The sample consisted of clinical hospital patients from different regions of the Republic of Croatia. Data collected from the normative sample were used for the calculation of norms. Norms for the MMPI-2 are presented in either linear or uniform T-scores. In view of the fact that the distribution of results of certain groups of MMPI-2 scales (clinical scales, content scales, content component scales and RC scales) is characterised by different degrees of positive asymmetry, uniform T-scores were calculated according to the method developed by Tellegen and Ben-Porath (1992) especially for the MMPI-2 in order to ensure the percentile comparison of results for these scales. In conclusion, the standardisation of the MMPI-2 in the Republic of Croatia was completed and Croatian norms were obtained.
Projekt MZOS
ENG